2009
DOI: 10.1308/003588409x358980
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic Management of Remnant Cystic Duct Calculi: A Retrospective Study

Abstract: INTRODUCTION Even though cholecystectomy relieves symptoms in the majority of cases, a significant percentage suffer from 'post-cholecystectomy syndrome'. Cystic duct/gall bladder remnant calculi is a causative factor. We present our experience with the laparoscopic management of cystic duct remnant calculi. PATIENTS AND METHODS We managed 15 patients with cystic duct remnant calculi from 1996 to 2007 in our institute. All these patients had earlier undergone laparoscopic subtotal cholecystectomy at our centre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
99
0
4

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 79 publications
(108 citation statements)
references
References 21 publications
5
99
0
4
Order By: Relevance
“…(6) Palanivelu C, Rangarajan M, Jategaonkar PA, et al observed that in Acute Cholecystitis with Cholelithiasis, sometimes a long cystic duct stump was left behind instead of dissecting too close to the common bile duct and right hepatic artery which again can be a predisposing factor for stone formation. (7) In Sezeur A and Akel K study, Cystic duct stone is found frequently during cholecystectomy, so the surgeon's team needs proper preoperative evaluation of the cystic duct and also careful ligation of the cystic duct at its junction from common hepatic duct. (8) Benninger J, Rabenstein T and Farnbacher M et al showed successfully managed post-operative cystic duct remnant stone by extracorporeal shockwave lithotripsy along with the endoscopic removal of the stone fragments.…”
Section: Discussionmentioning
confidence: 99%
“…(6) Palanivelu C, Rangarajan M, Jategaonkar PA, et al observed that in Acute Cholecystitis with Cholelithiasis, sometimes a long cystic duct stump was left behind instead of dissecting too close to the common bile duct and right hepatic artery which again can be a predisposing factor for stone formation. (7) In Sezeur A and Akel K study, Cystic duct stone is found frequently during cholecystectomy, so the surgeon's team needs proper preoperative evaluation of the cystic duct and also careful ligation of the cystic duct at its junction from common hepatic duct. (8) Benninger J, Rabenstein T and Farnbacher M et al showed successfully managed post-operative cystic duct remnant stone by extracorporeal shockwave lithotripsy along with the endoscopic removal of the stone fragments.…”
Section: Discussionmentioning
confidence: 99%
“…The follow-up period appears sufficient to capture almost all of the late complications associated with residual stones [40][41][42], but may be too short to detect problems associated with the remnant gallbladder, such as newly formed gallstones or postcholecystectomy syndrome [43].…”
Section: Discussionmentioning
confidence: 99%
“…This study reports the experience of using this device for removal of impacted stones in the cystic duct remnant. Most symptomatic patients with calculi in the cystic duct remnant undergo laparoscopic re-operation for stone management [17][18][19] . In this case, this peroral cholangioscopy system was used to place a guidewire in the cystic duct remnant under direct visualization after a failed attempt during ERCP, with subsequent removal of an impacted calculus.…”
Section: Discussionmentioning
confidence: 99%